Alcance y limitaciones de las consultorías en materia de seguridad pública y derechos humanos: es posible resistir a las generalizaciones y a los productos estandarizados?: relato de una experiencia = Outreach and limitations of the consultancies on public security and human rights: is it possible to resist generalizations and standardized products?: narrative of an experience - Pita, María Victoria; Miranda, Ana Paula Mendes de (Civitas - Revista de Ciências Sociais)
While notions of citizen security and political governance of security turned out to be political formulations with relative consensus in the region, it is well known that the processes through which these notions are embodied in the institutions are not linear. Decisions and practices in the process of register and production of information present various types of obstacles: some related on the nature of the data; others are customary practices of the participating agencies, and finally, there are cases of more or less explicit political and/or institutional resistance. In this paper we want to discuss about consultancy services that against the standardized models are able to produce reflections about state bureaucracies and the design of public policies as well as information and knowledge on the subject of citizen security and human rights